KONSEP KEADILAN EKONOMI DALAM TAFSIR AL-AZHAR: ANALISIS TERHADAP AYAT QS. AL-HASYR AYAT 7 - Cindy Rahmadhani Sinulingga; Syafii Syafii; Rudi Edwaldo Jasmit (STAI Asy-Syukriyyah, 2026)
This study aims to analyze the concept of economic justice in QS. Al-Hasyr verse 7 through the interpretation of Buya Hamka in Tafsir al-Azhar and to examine its relevance in the context of the modern economy. The method used is qualitative with a library research approach. The results show that QS. Al-Hasyr verse 7 emphasizes the importance of fair wealth distribution to prevent the concentration of wealth within certain groups, and positions ownership as a trust that carries social responsibility. Furthermore, economic justice in Islam is not only related to material aspects but also includes moral values such as justice, trustworthiness, and social responsibility. In the modern context, these principles remain relevant in addressing economic inequality and unjust distribution, and can serve as a foundation for building a more just, inclusive, and sustainable economic system.